An assessment of the Polar Weather Research and Forecasting (WRF) model representation of near‐surface meteorological variables over West Antarctica. Issue 4 (19th February 2016) - Deb, Pranab; Orr, Andrew; Hosking, J. Scott; Phillips, Tony; Turner, John; Bannister, Daniel; Pope, James O.; Colwell, Steve
Abstract: Despite the recent significant climatic changes observed over West Antarctica, which include large warming in central West Antarctica and accelerated ice loss, adequate validation of regional simulations of meteorological variables are rare for this region. To address this gap, results from a recent version of the Polar Weather Research and Forecasting model (Polar WRF) covering West Antarctica at a high horizontal resolution of 5 km were validated against near‐surface meteorological observations. The model employed physics options that included the Mellor‐Yamada‐Nakanishi‐Niino boundary layer scheme, the WRF Single Moment 5‐Class cloud microphysics scheme, the new version of the rapid radiative transfer model for both shortwave and longwave radiation, and the Noah land surface model. Our evaluation finds this model to be a useful tool for realistically capturing the near‐surface meteorological conditions. It showed high skill in simulating surface pressure (correlation ≥0.97), good skill for wind speed with better correlation at inland sites (0.7–0.8) compared to coastal sites (0.3–0.6), generally good representation of strong wind events, and good skill for temperature in winter (correlation ≥0.8). The main shortcomings of this configuration of Polar WRF are an occasional failure to properly represent transient cyclones and their influence on coastal winds, an amplified diurnal temperature cycle in summer, and a general tendency to underestimate the wind speed at inland sites in summer. Additional sensitivity studies were performed to quantify the impact of the choice of boundary layer scheme and surface boundary conditions. It is shown that the model is most sensitive to the choice of boundary layer scheme, with the representation of the temperature diurnal cycle in summer significantly improved by selecting the Mellor‐Yamada‐Janjic boundary layer scheme. By contrast, the model results showed little sensitivity to whether the horizontal resolution was 5 or 15 km. Key Points: Polar WRF is a useful tool for modeling West Antarctic climate Little sensitivity found between 5 and 15 km horizontal resolution MYJ boundary layer scheme gives better representation of diurnal cycle in near‐surface temperature